2014
DOI: 10.1177/1077546314561814
|View full text |Cite
|
Sign up to set email alerts
|

Optimal vibration control of beams subjected to a mass moving at constant speed

Abstract: This paper studies the optimal control of vibration of a beam excited by a moving mass. One important background of this work is vehicle-bridge interaction. As this is a time-varying system, some methods suitable for time-invariant systems are not always effective and will lead to suboptimal solutions when applied. In this particular vibration problem, the terminal time instant when the moving mass leaves the beam and the moving mass as the source of excitation are known. This particularity allows this problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The linear system represents the dynamics of a wide range of smart structures that can be controlled by integrated force actuators. Apart from the typical examples of such structures, namely, bridges and slender buildings exposed to earthquake or wind forces, offshore platforms subjected to sea waves or wind turbine blades exposed to wind flow which are controlled by means of electric motors or active tuned mass systems, we can also see new emerging designs that employ piezoelectric actuators and shape memory alloys or polymer‐based artificial muscles . In the present paper, we will consider a modular cantilever beam equipped with a set of electromagnetic force actuators.…”
Section: Distributed Control Designmentioning
confidence: 99%
“…The linear system represents the dynamics of a wide range of smart structures that can be controlled by integrated force actuators. Apart from the typical examples of such structures, namely, bridges and slender buildings exposed to earthquake or wind forces, offshore platforms subjected to sea waves or wind turbine blades exposed to wind flow which are controlled by means of electric motors or active tuned mass systems, we can also see new emerging designs that employ piezoelectric actuators and shape memory alloys or polymer‐based artificial muscles . In the present paper, we will consider a modular cantilever beam equipped with a set of electromagnetic force actuators.…”
Section: Distributed Control Designmentioning
confidence: 99%
“…affected by the three different types of acceleration curves when the acceleration (deceleration) time is equal to the swing period of the payload, as shown in Figure 2. Figures 6(a)-6(c), respectively; keeping these three maximum trolley acceleration values satisfies equation (18).…”
Section: Effect Of the Trolley's Acceleration On The Dynamicmentioning
confidence: 93%
“…It has been demonstrated that the dynamic behavior of the beam is affected by many parameters, such as the mass of the moving load [15], the load's acceleration [16,17], the load's speed [5,18], and many others. Extensive research has been done on the methods and efforts of limiting undesirable payload swing, such as an energy-based control scheme [19], input shaping technology [20], nonlinear coordination control [21], neural network control [22], fuzzy control [23], a trajectory planning method [24], and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Such bridge-vehicle system and gunprojectile system are generally taken as beam-moving mass systems (BMSs). [1][2][3][4] Recently, more and more attention has been attracted to optimal controller design of BMSs, such as time-varying optimal controller design in vehiclebridge interaction, 5 constant gain feedback gain design in vehicle-railway system, 6 the contribution of displacement-velocity feedback controller on the BMSs, 7 the influence of Lyapunov-based boundary controller on statically indeterminate beam 8 and the usage of a proportional-integral controller on the magnetic wheelsguide rail system. 9 Due to the uncertainties of system parameters and/or input disturbances, an optimal controller should be designed as uncertain.…”
Section: Introductionmentioning
confidence: 99%